2014
DOI: 10.2478/cpe-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Distribution of Chemical Compounds from Fly Ash Exposed to Weather Conditions

Abstract: The paper presents investigation results of the migration of a chemical compound contained in fly ash deposited on a dry furnace waste landfill site exposed to weather conditions. Climate conditions are able to significantly affect chemical component distribution in a block of deposited, moving chemical compounds to different depths. The main aim of the investigations was to determine the chemical component distribution of deposited fly ash in the landfill. Identification of chemical components based on XRF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…According to the America Society for Testing Materials (ASTM C618-05), the ash used in this study can be classified as Group F. The major components of fly ash were oxides of silicon and aluminium (Figure 1(b)), and various other oxides. This group has pozzolanic properties and are characterised by SiO 2 + Al 2 O 3 + Fe 2 O 3 > 70% and CaO < 10% (Sambor and Szymanek, 2014). Particle size analysis was shown for volume median diameter (d50) of about 33.3 μm, while (d10) and (d90) were 3.7 and 91.6 μm, respectively.…”
Section: Fly Ash (Fa)mentioning
confidence: 98%
See 1 more Smart Citation
“…According to the America Society for Testing Materials (ASTM C618-05), the ash used in this study can be classified as Group F. The major components of fly ash were oxides of silicon and aluminium (Figure 1(b)), and various other oxides. This group has pozzolanic properties and are characterised by SiO 2 + Al 2 O 3 + Fe 2 O 3 > 70% and CaO < 10% (Sambor and Szymanek, 2014). Particle size analysis was shown for volume median diameter (d50) of about 33.3 μm, while (d10) and (d90) were 3.7 and 91.6 μm, respectively.…”
Section: Fly Ash (Fa)mentioning
confidence: 98%
“…The share of dust and silt fractions determines filtrating and dusting properties. In gravel and sand fractions, irregular-forms, crumbs and conglomerates prevail; while in dust and silt fractions, regular smoothed particles are more common (Sambor and Szymanek, 2014). The small pore functional surface of FA was analysed non-destructively at all stages of the production process with confocal 3D microscope solutions.…”
Section: Fly Ash (Fa)mentioning
confidence: 99%
“…This is generally physical and chemical composition regarding volatile solids, total solids, C/N ratio as well as elemental analysis for carbon, nitrogen, hydrogen, and sulfur [71,72]. During substrate characterization, the place (source) where the substrate was collected is vital, as waste chemical content is affected by many factors, such as weather conditions and the type of soil where the original substances were grown [73,74]. Physical and chemical compositions depend on the type of substrate, for example, carbohydrates have carbon and hydrogen while proteins and lipids have nitrogen as part of their composition [75,76].…”
Section: Substrate Typementioning
confidence: 99%
“…The pozzolanic reactions were also noted. Sambor and Szymanek [ 19 ] analyzed almost 300 samples from the ash stockpile at a depth of 0–2.5 m exposed to the weather and found that the pH of the core borehole rose with its increasing depth, which resulted in alkaline reactions that promoted the leaching of chemical compounds into the stockpile. Several other works [ 20 , 21 ] indicate changes in the surface morphology of the deposited fly ash particles, namely the surface dissolution and the formation of new phases (secondary phases).…”
Section: Introductionmentioning
confidence: 99%